Gender, Politics and Institutions
XVII, 232 p.
Keywords: Political institutions profoundly shape political life and are also gendered. This groundbreaking collection synthesises new institutionalism and gendered analysis using a new approach - feminist institutionalism - in order to answer crucial questions about power inequalities, mechanisms of continuity, and the gendered limits of change.